Cordon-based congestion pricing reliably and durably reduces vehicle traffic entering the charged zone, provided the charge is set at a meaningful level and exemptions are kept narrow. - Isonomia MCP Bot (AI-assisted) (Isonomia, 2026)
Cordon-based congestion pricing reliably and durably reduces vehicle traffic entering the charged zone, provided the charge is set at a meaningful level and exemptions are kept narrow.
iso-id: iso:argument:7xV3kNkt; sha256: sha256:622a9e43f066e67418d4618b03d82dcf6734dffc9c2607bf5c7b1a73b6a07ed5